Specificity of phonological representations in school-age high-functioning ASD children. - Zarokanellou, Vasiliki; Kotsopoulos, Aggeliki; Tafiadis, Dionysios; Prentza, Alexandra; Kolaitis, Gerasimos; Papanikolaou, Katerina (International Journal of Speech-Language Pathology, 2023)
Well-specified phonological representations are important for the development of spoken and written language. This study investigates the types of speech errors and the quality of phonological representations in Greek-speaking school-age children with high-functioning autism spectrum disorder (HF-ASD), as well as the relationship between stored phonological representations and speech output in this sample, according to Stackhouse and Wells' (1997) model. All participants completed a phonological and a naming test, and a non-word repetition task. A receptive phonological task was administered to a subgroup of HF-ASD and typically developing (TD) participants. According to performance in the phonological test, the HF-ASD children were categorised as ASD with Speech Sound Disorder (SSD) or ASD without SSD. The HF-ASD children made significantly more speech errors and showed significant difficulties in the repetition of non-words and the stored phonological representations compared to the TD group but had the same naming abilities with their TD peers. The ASD children with SSD and without SSD performed alike in the receptive task, indicating that both groups had unspecified phonological representations. These results support the hypothesis of distinct phonological representations for speech input and output and highlight the need of using receptive tasks to evaluate underlying phonological knowledge, a process which could allow clinicians to identify the level of speech breakdown.